1990
DOI: 10.2105/ajph.80.6.730
|View full text |Cite
|
Sign up to set email alerts
|

Pawtucket Heart Health Program point-of-purchase nutrition education program in supermarkets.

Abstract: Point-of-purchase nutrition education in supermarkets is one intervention strategy of the Pawtucket Heart Health Program, a community cardiovascular disease prevention program in Pawtucket, Rhode Island.Using consumer intercept interviews, awareness of shelf labels and their effect on purchase behavior have been continuously evaluated. Between 1984 and1988, the percent of shoppers who could identify correct labels increased from 11 percent to 24 percent (95% confidence intervals of difference: 7,17). The perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…The evaluation results revealed a positive self-reported behavioural change from some mothers; this was further verified by increased sales of iron-rich infant food promoted in the display. The positive self-reported food choices demonstrated in this project are similar to results obtained in another community study that used a point-ofpurchase display (45). Community members rely on their grocery stores for most of their shopping needs.…”
Section: Discussionsupporting
confidence: 80%
“…The evaluation results revealed a positive self-reported behavioural change from some mothers; this was further verified by increased sales of iron-rich infant food promoted in the display. The positive self-reported food choices demonstrated in this project are similar to results obtained in another community study that used a point-ofpurchase display (45). Community members rely on their grocery stores for most of their shopping needs.…”
Section: Discussionsupporting
confidence: 80%
“…Three studies (42,46,50) referenced social marketing theory (51). Nine studies used environmental strategies (23,24,29,34,35,43,52–54) and 19 studies used nutrition education (23,24,29,31–33,35,3941,43,44,52–58) as both rationale and framework. The most frequently reported outcomes were awareness and use (17 studies) and knowledge and beliefs (18 studies), followed by sales data and process measures.…”
Section: Resultsmentioning
confidence: 99%
“…On average, randomized interventions had fewer points for effectiveness (0.7 points [range, 0–1]) than the 27 interventions that did not use randomization (1.4 points [range 0–3]) (24–28,3032,34–37,3946,50,52–54,56–58). …”
Section: Resultsmentioning
confidence: 99%
“…One intervention study found that food labelling increased consumers awareness of the labelled products over time; the shoppers also reported that they were encouraged to buy the identi®ed foods (Hunt et al, 1990). Another study showed that adult medical patients who ate less fat reported that food labels in¯uenced their food purchase decisions more compared to patients who ate more fat (Kreuter et al, 1997).…”
Section: Discussionmentioning
confidence: 99%